2022
DOI: 10.21203/rs.3.rs-1822955/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patient Journey for Hypertension and Dyslipidemia in Saudi Arabia: Highlighting the Evidence Gaps

Ashraf Amir,
Mirvat Alasnag,
Rajaa Al-Raddadi
et al.

Abstract: Background In recent years, Saudi Arabia has witnessed staggering rates of hypertension and dyslipidemia- related cardiovascular (CV) deaths, overburdening the healthcare ecosystem of the country. Appropriate public health interventions can be devised through quantitative mapping of evidence. Identification of potential data gaps can prioritize future research needs and develop a ‘best-fit’ framework for patient-centric management of hypertension and dyslipidemia. Methods This review quantified data gaps in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…A report from National Health and Nutrition Examination Survey in 2007–2008 showed that 20% of adults are unaware of their diagnosis of hypertension 24 . In a study in Saudi Arabia, the hypertension prevalence was reported to be 14%–41.8% and among hypertensives, 27.6%–61.1% were aware of their status 25 . The results of a meta‐analysis in India showed that the overall prevalence of hypertension in India was 29.8% 26 .…”
Section: Discussionmentioning
confidence: 99%
“…A report from National Health and Nutrition Examination Survey in 2007–2008 showed that 20% of adults are unaware of their diagnosis of hypertension 24 . In a study in Saudi Arabia, the hypertension prevalence was reported to be 14%–41.8% and among hypertensives, 27.6%–61.1% were aware of their status 25 . The results of a meta‐analysis in India showed that the overall prevalence of hypertension in India was 29.8% 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The HTN prevalence was 14.0-41.8%, while the dyslipidaemia prevalence was 12.5-62.0%. The HTN screening rate was 100%, but only 27.6-61% were aware, underwent diagnosis, received treatment, and achieved blood pressure (BP) control [9].…”
Section: Introductionmentioning
confidence: 99%